Caracterização química das polpas das espécies de açaí (Euterpe spp) - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The species E. precatoria, E. oleracea, E. oleracea var. green, belong to the genus Euterpe of the family Arecaceae (Palmae). They are chemically characterized by having carotenoids; flavonoids; phenolic compounds; catechin; quercetin; gallic acid; routine; coumaric acid; ferulic acid; chlorogenic acid; quinic acid; caffeic acid; anthocyanins, among other derived substances. Due to this range of assets, its benefits to human health are promising, having biological effects such as antioxidant, anti-inflammatory, neuroprotective. Its pulp is the most consumed product in the North Region, and has been winning the international market. In this context, the research aims at the investigation and chemical characterization of extracts obtained from different species of the genus Euterpe spp. In the present study, the composition of five hydroalcoholic extracts of açaí species, collected in the municipality of Coari-Am, was analyzed, evaluating antioxidant activities against the ABTS•+ radical and DPPH. Biological tests were performed to quantify total phenols and total flavonoids. The characterization of the extracts was performed by chromatographic methods, being CCD thin layer chromatography and by mass spectrometry. The results show good separation of substances when analyzed in TLC, as they are species of the same genus, the presence of phenols and flavonoids was observed in the analyzed species, being more intense in the species E. oleracea, corroborating with the literature. When submitted to antioxidant tests, the extracts had better results against the ABTS•+ radical than DPPH. In the chemical/biological tests, species of the genus Euterpe showed positive results in the qualitative inhibition of the DPPH radical, presenting IC50 values of 70.1 and 64.3 for EHEP and EHPPL respectively. In the ABTS method we can highlight the values for the extracts of E. precatoria (EHEP and EHPPL) 41.6±3.0, 39.8±0.1 respectively. For E. oleracea var. green resulted in the following IC50 values respectively of DPPH and ABTS 216.3 ± 6.7; 58.8±1.9. In the analyzes of total phenols and flavonoids when compared with their respective standard. For total flavonoids, average inhibition values of 55% and 70% were obtained, respectively for the extracts of EHEO, EHEOPL, while for the species of E. precatoria, values of 57% for the EHEP extract and 66% were expressed. for the EHEPPL lyophilized pulp extracts and for the E. oleracea var. green percentage 38%. Compared to the standard that had an inhibition value of 64%, the E. precatoria extracts were more similar to the standard used. And for the tests of total phenols, the results express the percentage of inhibition that were 24%, 12%, 10%, 19% and 12% for EHEP, EHEO, EHEOv, EHEPPL and EHEOPL, respectively, compared to the standard that expresses the percentage of 47%. By analyzing mass spectral data, it was possible to characterize and identify some substances that corroborate the literature. Highlighting the ions 449.11; 287.06; 593.15; 611.16; 609 found for the species of E. precatoria, and ions for E. oleracea 449.11; 431.24; 447.09; 299.05; 609. In addition to the species of E. oleracea var. green and their respective ions 461; 299.05;447.09; 431.19. During the preparation of the formulations and physical-chemical tests, the phytocosmetics remained stable and had a good acceptance during the sensorial analysis.
Keywords: Compostos bioativos das plantas; Produtos vegetais - Análise; Açaí; CIENCIAS BIOLOGICAS; Açaí; Análise química; Bioativos; Antioxidantes